Penerapan dasar perhitungan kebutuhan katalisator untuk oksidasi sulfida - Suryaningsih, Puji Ediari (Majalah Kulit, Karet, dan Plastik, 1994)
Sulphides beared in tannery wastewater are harmful pollutant which beturned to disastrous hydrogen sulphide gas under acidic circumtances. The previous study on Sulphides Oxydation System of varied catalist (MnSO4) added has not indicated a satisfactory result yet. The main objective of this study is to verify the merit of Mn++ dosage based on the sulphides content. Futher, whether or not it will be useful to optimize the oxydation process and economize the daily cost of tannery wastewater treatment. The data of sulpides content monitored during 12 hours oxidation period showed that there was significant difference between the curve (sulpides vs time) with Mn++ and the curve without Mn++ treated as the control. When a foamy oxydated wastewater appeared such as liming waste it would be a problem and the foam should be removed in such a way that not to be harmfull to the oxidation and other chemical processes. However, anti foam substance must be provided or introduced to clean Technology in the system. The experiment, observation and chemical tests data of this study gives proves the advantages of adding Mn++ in sulphides  oxidation system. The catalist adding based on the sulphides content can be considered realistic.     INTISARI Sulfide yang terkadang dalam air limbah penyamakan kulit dapat berbahaya jika berubah menjadi gas H2S dibawah kondisi asam. Penelitian sebelumnya yang memvarisi penambahan Mn SO4 sebagai katalisator oksidasi sulfida belum menunjukkan hasi yang mantap. Adapun tujuan penelitian ini adalah untuk memastikan dosis penambahan MnSO4 kedalam system oksidasi sulfida sehingga dapat digunakan sebagai patokan. Kegunaan dari dosis optimum adalah untuk menghemat biaya operasional harian pada unit pengolah air limbah. Data kandungan sulfide yang dimonitor dalam 12 jam menunjukkan perbedaan nyata antara curva oksida (sulfide vs waktu) dengan Mn++ dan cuva oksidasi yang tanpa Mn ++ sebagai kontrol. Jika air limbah yang berbuih diokidasi dengan cara ini maka akan menimbulkan masalah, akan tetapi masalah buih dapat diatasi dengan ati buih sejauh tidak menganggu proses pengolahan atau bahkan menambah zat cemaran. Penelitian ini menunjukkan data uji yang positip menguntungkan dengan penambahan katalisator Mn++ pada sistem oksidasi sulfida.